Menerapkan Thaharah untuk Mewujudkan Gaya Hidup Bersih dan Berbudaya - Muhammad Haikal Hodila; Ikhsan Al Khifari; Aman Dariyanti; Sifa Hayatul Husna; Najwa Ananda Putri; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
The principle of thaharah reflects the values ​​of cleanliness and purity in the daily lives of Muslims, emphasizing the importance of protecting oneself from things that are considered unclean both physically and spiritually. This research aims to provide an in-depth understanding of the concept of Taharah and the importance of its practice in everyday life -day, as well as explaining the health benefits and changes in individual behavior that can be obtained by practicing Taharah to increase awareness. Implementing Taharah and educating the public about the Taharah concept and its implementation. The research method used in this research is a qualitative technique with a descriptive approach. Data collection was carried out in the form of library research. This research was carried out by reading and reviewing bibliographic information in the form of books and scientific journals regarding the practice of Taharahh in living a clean and cultured life. The results of this research discussion provide a deeper understanding of the factors that influence the use of Taharahh in everyday life and how it can be achieved. impact on your overall quality of life. By involving individuals, families, communities and government, the implementation of Taharah brings real benefits in living a clean and civilized life and creating a healthy, clean and civilized society.